The Life Model of Nisargadatta Maharaj as Interpreted by Ramesh Balsekar - Gejza M. Timčák (Spirituality Studies, 2015)
Ramesh Balsekar (1917–2009) was a disciple of Nisargadatta Maharaj (1897–1981). Nisargadatta Maharaj lived in Bombay and taught what he realized: For doing our dharma everything is provided for us. Thus we can focus our attention on discovering “Who one is“ and let life flow. In 1996 the author of this article had a short conversation with Ramesh Balsekar, who presented his way of understanding the teaching of Nisargadatta Maharaj.